Membangun Kembali Nilai-Nilai Dasar Keislaman sebagai Resolusi Konflik Ahmadiyah: Diskursus Hak Kebebasan Beragama dan Berkeyakinan - Dedi Putra (Nizham Jurnal Studi Keislaman, 2017)
Justice, tolerance, and mutual forgiveness is the fundamental values of Islam. Theprinciple must be understood and imitated and realized in social attitudes. But infact, the principle of nonviolence and peace in Islam was limited to the principle ofnot integral to the individual Muslim. This has often resulted in various conflictsin society. This paper focuses existence of Ahmadiyah conflict. Ahmadiyahposition as a minority group should get protection from the state. The State mustensure and protect the rights of religious freedom which is owned by Ahmadiyah.So with the protection provided by the state, the new state acts can be said to be inaccordance with the constitutional mandate.